THE METHODS OF CONTEMPORARY PHILOSOPHY IN RESEARCH OF INTERCULTURAL EDUCATION - Morschinska, U.; Morschinski, V. (Continuing Professional Education: Theory and Practice, 2019)
The intercultural education is comprehended as a dialogue which is focused on agreement. Its effect is mutual enriching the neighbouring cultures. The model of such a dialogue can be analysed by the using the methods of philosophy. Hermeneutics allows to establish the historic situation of the dialogue; analytic philosophy provides ways of speech acts analysis; phenomenology shows the principles of research of axiological aspect of communication. The philosophical ways of examining the dialogue could be thus helpful in pedagogical research and in educational practice. Philosophical research methods have two aspects: cognitive and practical, which can be useful in the diagnostics of the educational situation and understanding how to create the conditions that are necessary for the implementation of the multicultural education. Examining multicultural education as a dialogue that aimed at the understanding of the truth, it is determined the need to undertake a study in various areas of the philosophy. The researches may be conducted at the different levels and based on the methods of language analysis, phenomenological methods, axiological aspects, hermeneutic understanding and normative concept of speech.